Inventory of managed aquifer recharge sites in Europe: historical development, current situation and perspectives - Sprenger, C.; Hartog, N.; Hernández, M.; Vilanova, E.; Grützmacher, G.; Scheibler, F.; Hannappel, S. (Hydrogeology journal, 2017)
Different types of managed aquifer recharge (MAR) schemes are widely distributed and applied on various scales and for various purposes in the European countries, but a systematic categorization and compilation of data has been missing up to now. The European MAR catalogue presented herein contains various key parameters collected from the available literature. The catalogue includes 224 currently active MAR sites found in 23 European countries. Large quantities of drinking water are produced by MAR sites in Hungary, Slovakia, the Netherlands, Germany, Finland, Poland, Switzerland and France. This inventory highlights that, for over a century, MAR has played an important role in the development of European water supply and contributes to drinking-water production substantially. This development has occurred autonomously, with “trial-and-error” within the full range of climatically and hydrogeologically diverse conditions of the European countries. For the future, MAR has the potential to facilitate optimal (re)use and storage of available water resources and to take advantage of the natural purification and low energy requirements during MAR operations. Particularly with respect to the re-use of wastewater treatment-plant effluent and stormwater, which is currently underdeveloped, the use of MAR can support the public acceptance of such water-resource efficient schemes. Particularly for the highly productive and urbanized coastal zones, where the pressure on freshwater supplies increases by growing water demand, salinization and increased agricultural needs for food production (such as along the Mediterranean and North Sea coasts), MAR is expected to be increasingly relied on in Europe.